Navigating and making sense of urgent and emergency care processes and provision - Pope, C; McKenna, G; Turnbull, J; Prichard, J; Rogers, A (Wiley, 2019)
Background: Whilst many health systems offer a range of urgent and emergency care services to deal with the need for unscheduled care, these can be problematic to navigate. Objective: To explore how lay people make sense of urgent care provision and processes. Design: Qualitative study, incorporating citizen panels and longitudinal semi‐structured qualitative interviews. Setting and Participants: Two citizens’ panels, comprising purposively selected public populations—a group of regular users and a group of potentially marginalized users of urgent and emergency care. Semi‐structured interviews were conducted with 100 people, purposively sampled to include those over 75, aged 18‐26 years, and from East/Central Europe. A sub‐sample of 41 people received a second interview at +6‐12 months. Framework analysis was thematic and comparative, moving through coding to narrative and interpretive summaries. Findings and Discussion: Participants narratives illuminated considerable uncertainty and confusion regarding urgent and emergency care provision which in part could be traced to the contingent nature of urgent and emergency care need. Accounts of emergency care provision were underpinned by strong moral positioning of appropriate help‐seeking, demarcating legitimate service use that echoed policy rhetoric, but did not necessarily translate into individual behaviour. People struggled to make sense of urgent care provision making navigating “appropriate” use problematic. Conclusions: The focus on help‐seeking behaviour, rather than sense‐making, makes it difficult to move beyond the polarization of “appropriate” and “inappropriate” service use. A deeper analysis of sense‐making might shift the focus of attention and allow us to intervene to reshape understandings before this point.